Pilot-Based Codebook Non-Orthogonal Artificial Noise Schemes for Physical Layer Security: Secrecy Capacity Optimization Under Unknown Eavesdropper Channels - Yi Zhang; Yebo Gu; Tao Zhao; Bo Wang (IEEE Access)
Non-Orthogonal Artificial Noise (NORAN) has garnered significant attention in modern communication systems as a substitute for traditional Artificial Noise (AN), due to its independence from channel degrees of freedom. However, the design of NORAN leads to a reduction in the channel capacity of legitimate channels, thereby limiting its application in practical systems. Pilot-based Codebook Non-Orthogonal Artificial Noise (PCAN) leverages pilot signals exchanged between the receiver and transmitter as encryption keys. This allows the receiver to retrieve the upcoming PCAN from the codebook via the pilot signals, effectively transitioning from NORAN to AN in form, demonstrating high adaptability. Consequently, this paper investigates the deployment of PCAN in Massive MIMO systems to achieve secure communication. Considering the eavesdropper as an illegitimate user, whose channel state information matrix is unknown to the legitimate receiver and does not follow a simple distribution pattern, this study employs random matrix theory to model the channel of an unknown eavesdropper. It uses the successive convex approximation algorithm to analyze the optimal power allocation strategy and the maximum number of eavesdropper antennas that the system can tolerate under these conditions. The findings indicate that as the number of eavesdropper antennas increases, the eavesdropper channel modeling based on random matrix theory increasingly approximates the actual channel characteristics of the eavesdropper. Notably, when the number of eavesdropper antennas $N_{E} = 128$ , the consistency between the modeled channel and the actual channel reaches 87.2%, and the optimal power allocation factor at this point is $θ = 0.5$ . However, as the number of eavesdropper antennas continues to increase, the effectiveness of PCAN becomes more pronounced. Nevertheless, when the number of eavesdropper antennas approaches infinity, the efficacy of PCAN significantly decreases, failing to adequately ensure the system’s security.